Relação entre o raciocínio lógico e o raciocínio matemático - Silva, Simone de Oliveira Andrade (2017)
The aim was to identify possible relationship between logical reasoning and mathematical reasoning in children between 9 and 10 years old. Twenty-six children were recruited from an elementary school. They were distributed in two different groups: high and low performance in arithmetic mathematics. An instrument was applied to collecting data. It was composed of five set of problems: two to assess mathematical reasoning and three to assess logical reasoning. Three descriptions for analyses: participants performance outcomes; categorization of participants explanation about their reasoning to solving those problems and; instrument. The results evidenced strong correlation between logical reasoning and mathematical reasoning. The categorization of participants explanation indicated strong incorrect control by presence/absence of number in the mathematics problems and strong incorrect control by statement in problems that involve logic. The instrument was useful to register and analyze difficulties of the participants in solving the items. It is suggested insert qualitative analysis in the teacher assessment to understand student performance. It is advised to add to elementary school education and to teacher training the teaching of logic